Computación de alto desempeño en GPU : EDULP, 2011. ISBN 978-950-34-0759-2 - Piccoli, María Fabiana (2012)
Through this textbook (written in Spanish), the author introduces the GPU as a parallel computer that is able to solve general-propose problems. The book has a didactic approach, it includes the first steps to CUDA programming, some tips to take account to develop good applications performance, many examples and exercises.